Effects of parent–child interaction training on children who are excessively exposed to digital devices: A pilot study. (November 2019) - Sadeghi, Saeid; Pouretemad, Hamid Reza; Khosrowabadi, Reza; Fathabadi, Jalil; Nikbakht, Sedighe
Objective: In the last decade, the use of digital devices among children has increased. This study examines the effects of parent–child interaction training on the amount of time children use digital devices, conflict and closeness in parent–child relationships, executive functions, and the electroencephalogram absolute power in children who excessively use the digital devices. Method: The sample group consisted of 12 children (24 to 47 months) who spent more than half of their waking hours using digital devices. Parents were trained to intensive interaction with the child for two months. Electroencephalogram absolute power, parent–child interaction, the amount of time children use digital devices, and children's executive function skills were assessed. Results: Parent–child intensive interaction reduces the use of digital devices; decrease the conflicts and increase the closeness in parent–child relationships; decrease executive functioning problems; and increase the absolute power of alpha and alpha 2 (F3), beta 1 (F3), and beta and beta 2 (F3, Fp2). Conclusion: These findings provide evidence of the negative effects of the excessive use of digital devices in children, the importance of parent–child interaction, and its positive impacts on cognitive and brain functions in children. It might contribute to better understand the importance of parent–child interaction in the early years.